Phylogenetic study of polypores mushroom in Peninsular Malaysia - Hoo, Yip Soon.
Phylogenetic tree was supposely constructed to cluster samples of polypores taken from various locations in Peninsular Malaysia using molecular technique. In this study, Polymerase Chain Reaction (PCR) will be used to detect polymorphism in the genetic level. These polymorphism occur due to mutation and being passed onto the next generation by inheritance. By choosing the gene that is conserved among the polypores, we can discriminate genetic differences them. Gene chosen in this project are the small subunit rRNA (18S rDNA) gene and the ITS region within the rDNA. Both genes will be amplified using common primer set NS3/NS6 (18S rDNA) and ITS1/ITS4 (ITS region). PCR product will then be subjected to purification and sequencing. However, the lack of satisfactory data results the inability to construct a phylogeny tree. This is a result of the unsuccessful optimization in PCR and DNA extraction.